The role of maternal anorexia nervosa and bulimia nervosa before and during pregnancy in early childhood wheezing: Findings from the NINFEA birth cohort study. Issue 8 (2nd May 2018) - Popovic, Maja; Pizzi, Costanza; Rusconi, Franca; Gagliardi, Luigi; Galassi, Claudia; Trevisan, Morena; Merletti, Franco; Richiardi, Lorenzo
Abstract: Objective: This study evaluates associations of maternal eating disorders (bulimia nervosa, anorexia nervosa, and purging behaviors) with infant wheezing and examines the effects of eating disorders on several wheezing determinants. Method: We studied 5, 150 singletons from the NINFEA birth cohort. Maternal bulimia nervosa and anorexia nervosa diagnoses were ascertained from the questionnaires completed in pregnancy and 6 months after delivery, and were analyzed as: ever diagnosis, only before pregnancy, and during pregnancy. Purging behaviors were assessed for 12 months before or during pregnancy. The associations with wheezing between 6 and 18 months of age were assessed in models adjusted for a priori selected confounders. Results: Children born to mothers with lifetime eating disorders were at an increased risk of developing wheezing (adjusted OR 1.68; [95% CI: 1.08, 2.60]), and this risk further increased when the disorders were active during pregnancy (2.52 [1.23, 5.19]). Increased risk of offspring wheezing was observed also for purging behaviors without history of eating disorder diagnosis (1.50 [1.10, 2.04]). The observed associations were not explained by comorbid depression and/or anxiety. Bulimia nervosa and/or anorexia nervosa during pregnancy were also associated with several risk factors for wheezing, including maternal smoking, adverse pregnancy outcomes, shorter breastfeeding duration, and day‐care attendance. Discussion: The associations of maternal eating disorders with offspring wheezing suggest long‐term adverse respiratory outcomes in children of mothers with eating disorders. A better understanding of mechanisms implicated is necessary to help reduce the respiratory disease burden in these children.